Endovascular treatment of middle cerebral artery aneurysms: current status and future prospects - Zhou, Zibo; Lan, Wenjing; Yu, Jinlu (Frontiers in Neurology, 2023)
Middle cerebral artery (MCA) aneurysms are complex and widely distributed throughout the course of the MCA. Various types of aneurysms can occur in the MCA. Ruptured as well as unruptured MCA aneurysms may require treatment to avoid bleeding or rebleeding. Currently, clipping is regarded as the first-line choice for the treatment of MCA aneurysms. However, endovascular treatment (EVT) is emerging as an alternative treatment in selected cases. EVT techniques vary. Therefore, it is necessary to review EVT for MCA aneurysms. In this review, the following issues were discussed: MCA anatomy and anomalies, classifications of MCA aneurysms, the natural history of MCA aneurysms, EVT status and principle, deployments of traditional coiling techniques and flow diverters (FDs), and deployments and prospects of intrasaccular flow disruptors and stent-like devices. According to the review and our experience, traditional coiling EVT is still the preferred therapy for most MCA aneurysms. FD deployment can be used in selective MCA aneurysms. Parent artery occlusion (PAO) can be used to treat distal MCA aneurysms. In addition, new devices can be used to treat MCA aneurysms, such as intrasaccular flow disruptors and stent-like devices. In general, EVT is gaining popularity as an alternative treatment option; however, there is still a lack of evidence regarding EVT, and longer-term data are not currently available for most EVT devices.